2007
DOI: 10.2807/esw.12.48.03318-en
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of measles cases in northern Italy: a preliminary report

Abstract: From 19 September to 19 November 2007, 46 measles cases related to a single outbreak were reported in the Piemonte region of northern Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Despite the increase of vaccination coverage and decrease of measles incidence, several outbreaks have occurred in Italy in recent years [8][9][10][11][12], as in other European countries including Romania, Germany, UK and Switzerland [13].…”
mentioning
confidence: 99%
“…Despite the increase of vaccination coverage and decrease of measles incidence, several outbreaks have occurred in Italy in recent years [8][9][10][11][12], as in other European countries including Romania, Germany, UK and Switzerland [13].…”
mentioning
confidence: 99%
“…The epidemiological analysis indicated the independent introduction of two measles viruses spreading in other epidemic areas, i.e. Piedmont [10, 11] and Germany [21, 22]. In both outbreaks the index case was linked to educational settings where the virus affected a small number of susceptible subjects.…”
Section: Discussionmentioning
confidence: 99%
“…the universal second dose at 5-6 years and a catchup of children attending primary school [5][6][7][8]. Despite these efforts and the considerable decrease of morbidity since 1995, measles is still endemic in Italy and since 2006 a number of outbreaks have occurred in a number of regions, namely Apulia, Lazio and Piedmont ; these outbreaks were caused by two distinct genotypes, D4 and B3 [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This supposition was supported by subsequent epidemiologic investigation that showed that measles was not circulating in this region of Northern Italy before the index case returned from the United Kingdom, and an outbreak occurred subsequent to her return. Example 2 was adapted from the index case in Filia et al 11 Example 3: a healthcare worker develops SARS from an unknown exposure. A healthcare worker developed SARS symptoms on March 28, 2003, with no known occupational exposure to SARS (Figure 3).…”
Section: Individual Investigationsmentioning
confidence: 99%